The impact of economic growth and energy consumption on carbon emissions: Evidence from panel quantile regression - Yefan Zhou (2018)
© Published under licence by IOP Publishing Ltd. This study investigates the impact of economic growth and energy consumption on carbon emissions in ten top selected countries contributing to the total carbon emissions in the world with an aim to test the validity of the Environmental Kuznets Curve (EKC) hypothesis, including five developing countries (China, India, Brazil, Mexico and South Africa) and four developed countries (European Union, the United States of America, Canada and Japan). This paper adopts a panel quantile regression model that takes unobserved individual heterogeneity and distributional heterogeneity into consideration. Moreover, to avoid an omitted variable bias, certain related control variables are included in our model. Our empirical results show that the effect of the independent variables on carbon emissions is heterogeneous across quantiles. Energy consumption increases the carbon dioxide emissions, with the strongest effects occurring at different quantiles for sample groups data. But the effects of energy consumption on carbon emissions for developed countries are greater than developing countries. In view of the economic development, developing countries and developed countries present the obvious stage characteristics. The empirical findings are in support of inverted U-shaped curve of the in the selected countries.